The Pastoral Epistles - Kelly, John Norman Davidson (Grand Rapids, MI Baker, 1969)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Peter -- commentaries; Bible. N.T. Jude -- commentaries